Age-dependent regulation of host seeking in Anopheles coluzzii - Omondi, Bonaventure Aman Oduor; Ghaninia, M.; Dawit, M.; Svensson, T.; Ignell, R. (Springer, 2019)
Behavioural attraction of the malaria vector Anopheles coluzzii to human host odour increases during adult maturation. We have previously demonstrated that the onset of host seeking in An. coluzzii coincides with an increased sensitivity of the CO2-sensitive neurons and abundance of chemosensory receptor gene transcripts in the maxillary palp. In this study, we extend our analysis to the antenna. Functional characterisation of the near-complete repertoire of odorant receptors (Ors) expressed in this tissue, to fractioned human odour, reveals a subset of salient human odorants to be detected by Ors at physiological relevant concentrations. When presented as a blend in their ratio of natural emission, these odorants elicit attraction by host-seeking mosquitoes, emphasising that Ors alone can mediate this behaviour. However, the same blend inhibits attraction in teneral mosquitoes. This switch in behavioural response indicates a change in valence during adult maturation. Quantitative analysis of Or transcript abundance and in vivo electrophysiological analysis reveal that the olfactory system of female An. coluzzii undergoes concerted changes that correlate with the onset of host seeking. We conclude that changes in Or abundance modulate peripheral olfactory coding, resulting in ecologically relevant behavioural effects.